I'LL NO LONGER BE A CAPULET: ARCHETYPAL SHIFTS IN THE MOVIE AND ANIME ADAPTATIONS OF SHAKESPEARE'S JULIET - Futiha Alambarra Amaan Ahmada; Ntamwana, Simon (CrossOver, 2024)
Adaptation is being a striking phenomenon that attracts many people because it tends to produce a different sensation of the source text. This research considers this phenomenon in order to reveal the shifts between the source text and the adaptation versions. The article is a comparative study that applies the archetypal theory. It sets out to reveal the similarities and differences with respect to the archetypes pertaining to the Juliet character in Shakespeare’s play, Romeo and Juliet, and its film and anime adaptations. The descriptive qualitative method is used to enable the researcher to do the interpretation and descriptive analysis. Moreover, the research uses the theory of structuralism and archetypal characters by Mark and Pearson. The theory of archetypal character draws from twelve primary archetypes to find and analyze the data through some dialogues and passages of the story. The archetype shifts in Juliet's character are identified by comparing three texts, including William Shakespeare’s Romeo and Juliet (second quarto version), Baz Luhrman’s Romeo + Juliet (1996), and Fumitoshi Oizaki’s Romeo x Juliet (2007). It is discovered that the archetypal character of Juliet shifts in the three analyzed texts. Based on the function of the character, the archetype of Juliet the Lover is maintained in Luhrmann’s Romeo + Juliet. Nonetheless, in Oizaki’s Romeo x Juliet, it changes into Juliet the Hero.